Neuroblastoma: Diagnostic and Clinical Aspects - Marino, Silvia; Puglisi, Federica; Magro, Gaetano; Belfiore, Giuseppe; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Portale, Anna; D'Amico, Salvatore; Miraglia, Vito; Licciardello, Maria; Lo Nigro, Luca; La Spina, Milena; Russo, Giovanna; Di Cataldo, Andrea (Journal of Pediatric Biochemistry, 2015)
Due to its many clinical and biologic characteristics, neuroblastoma (NB) is a polyhedric neoplasm. It is a very complex, extremely heterogeneous disease that can regress spontaneously even without therapy. However, it frequently shows a very aggressive behavior, refractory to current intensive multimodal therapy. The tumor, originating from primordial neural crest cells, is biochemically unique for its metabolic pathways of catecholamine synthesis and metabolism. Homovanillic acid (HVA), the main metabolite of dopamine, and vanillylmandelic acid (VMA), the main metabolite of adrenalin and noradrenalin, are sensitive and convenient markers of NB since they are found in large amounts in patient's urine. The rate of NB patients with positive VMA and/or HVA at the diagnosis varies with the stage of the disease, with high-stage tumors being more likely to have abnormal levels. Other less specific NB tumor serum markers are neuron-specific enolase, ferritin, and lactate dehydrogenase. NB is one of the few pediatric tumors in which tumor markers have been shown to have a role in the diagnosis, prognosis, and disease monitoring.
Keywords: neuroblastoma; homovanillic acid; vanillylmandelic acid; neuron-specific enolase; ferritin; lactate dehydrogenase